Troubling Metaphors and International Student Adjustment: Reflections from a Transnational Place - Starr-Glass, David (Journal of International Students, 2017)
On many campuses, offices of International Student Affairs address the perceived needs of international students. However, a number of underlying assumptions and persistent metaphors shape these efforts and influence their outcomes. All students are uniquely different and face equally different challenges in adjusting to higher education. Labeling students “international” may make institutional sense, but it can potentially hinder their transition, adjustment, and ultimate success. Applying restrictive labels can perpetuate stereotypes, reinforce institutional silos, and potentially fracture international students from the rest of the student body. This article reflects on how students—irrespective of national origins—are viewed and assisted in a transnational setting that includes more than 70% of students who might, in other contexts, be classified as “international.”